2019
DOI: 10.1084/jem.20190950
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA-encoded polypeptide ASRPS inhibits triple-negative breast cancer angiogenesis

Abstract: Triple-negative breast cancer (TNBC) is a subtype of breast cancer (BC) with the most aggressive phenotype and poor overall survival. Using bioinformatics tools, we identified LINC00908 encoding a 60–aa polypeptide and differentially expressed in TNBC tissues. We named this endogenously expressed polypeptide ASRPS (a small regulatory peptide of STAT3). ASRPS expression was down-regulated in TNBCs and associated with poor overall survival. We showed that LINC00908 was directly regulated by ERα, which was respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
101
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(112 citation statements)
references
References 46 publications
(53 reference statements)
0
101
0
1
Order By: Relevance
“…The lncRNAs are a newly recognized mechanism for gene regulation and are being explored as potential therapeutic targets in a variety of diseases (Li et al, 2018;Pecero et al, 2019;Wang et al, 2020), including diabetic nephropathy (Ge et al, 2019;Yang et al, 2019). A nucleic acid-based approach could allow greater specificity than pharmacological compounds, reducing side effects and allowing tissue-specific delivery (Sharma and Watts, 2015;Ku et al, 2016).…”
Section: Figure 8 | Ko Of Edn1-as Regulatory Elements Results In Incrmentioning
confidence: 99%
“…The lncRNAs are a newly recognized mechanism for gene regulation and are being explored as potential therapeutic targets in a variety of diseases (Li et al, 2018;Pecero et al, 2019;Wang et al, 2020), including diabetic nephropathy (Ge et al, 2019;Yang et al, 2019). A nucleic acid-based approach could allow greater specificity than pharmacological compounds, reducing side effects and allowing tissue-specific delivery (Sharma and Watts, 2015;Ku et al, 2016).…”
Section: Figure 8 | Ko Of Edn1-as Regulatory Elements Results In Incrmentioning
confidence: 99%
“…51 In addition, long ncRNA encoded 60-amino acid polypeptide (ASRPS), centromere protein U, endogenous hydrogen sulfide, and exosomal-annexin A2 have been found to be associated with angiogenesis and suggested to be potential targets. [52][53][54][55]…”
Section: Angiogenesis Inhibitorsmentioning
confidence: 99%
“…The regulatory mechanisms of lncRNA vary depending on their location in the nucleus or cytoplasm ( 17 ). Numerous studies have reported that lncRNAs serve key roles in pathogenesis of various diseases, including cancer, cardiovascular diseases, nervous system disease and immune diseases ( 18 - 21 ). Certain lncRNAs are involved in autoimmune diseases, such as multiple sclerosis, rheumatoid arthritis (RA) and systemic lupus erythematosus (SLE) ( 22 - 24 ).…”
Section: Introductionmentioning
confidence: 99%